Need for good pharmacy practice compliance in community pharmacies of nepal: its challenges and opportunities - Sabina Sankhi; Nirmal Raj Marasine (Discover Public Health)
Abstract Community pharmacies in Nepal serve as vital access points for healthcare services and medication. However, compliance with Good Pharmacy Practice (GPP) standards remains suboptimal despite the existence of national guidelines and regulatory frameworks. This perspective highlights the need for GPP implementation, identifies key challenges, and outlines the potential opportunities associated with effective compliance. Major barriers include limited awareness of GPP standards, weak regulatory enforcement, unauthorized personnel, financial constraints, and public misconceptions about the pharmacists role. Additionally, factors such as high workloads, inadequate infrastructure, and lack of incentives further hinder compliance. Nonetheless, GPP adoption offers significant benefits: promoting rational drug use, enhancing patient safety, and strengthening pharmacists role in healthcare delivery. It also promotes transparency, professional development, and alignment with global pharmacy standards. Strengthening regulatory oversight, advancing professional education, and raising public awareness are essential to overcoming current barriers. Effective GPP implementation can standardize community pharmacy services and elevate Nepal’s healthcare system to meet international quality benchmarks.